Reliability of modified-modified Schober’s test for the assessment of lumbar range of motion - Amjad, Fareeha; Mohammad Ali Mohseni Bandpei; Syed Amir Gilani; Arooj, Ayesha (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the intra-rater reliability of modified-modified Schober’s test for measuring lumbar flexion and extension in patients of lumbar radiculopathy. Method: The case-control reliability study was conducted at the University of Lahore Teaching Hospital, Lahore, Pakistan, from March to September 2020, and comprised lumbar radiculopathy patients of either gender aged 35-60 years in group A and healthy controls in group B. Lumbar flexion and extension were measured by the same examiner on three different occasions. A non-stretching measuring tape was used in which the first two measurements were taken using the modified-modified Schober’s test on the same day with a difference of 5 minutes, and the third measurement was taken three days later to assess reliability. To assess the test-retest reliability, intraclass correlation coefficient was calculated through two-way random analysis of variance. Standard error of measurement and minimal detectable change were also calculated. Data was analysed using SPSS 25. Results: Of the 40 subjects, 20(50%) were in group A with a mean age of 45.00+/-6.72 years, and 20(50%) were in group B with a mean age of 49.60+/-6.65 years. Overall, there were 16(40%) male and 24(60%) female subjects. Within-day lumbar flexion and extension measurements were highly reliable in controls (intraclass correlation coefficient 0.93 for flexion and 0.96 for extension) as well as in patients (intraclass correlation coefficient 0.94 for flexion and 0.95 for extension). —Continue